The Nature of the Shi'ra Star Qs. Al-Najm Verse 49 (Thantawi Jauhari's Perspective in TafsiR Al-Jawahir Fi Tafsir Al-Qur'an Al-Karim - Fauzi Fathur Rosi; Rofiatul Muna (Penerbit Hellow Pustaka, 2025)
In essence,the Qur’an and natural phenomena are one unit. The verses written in the koran are called qouliyyah verses, and the natural phenomena that appear in the universe are called kauniyyah verses. The Al-Qur’an, which has been written and recorded since 1.400 years ago, has inspired many scientists in various parts of the world. Various cases of current scientific problems have been discovered through scientific signs in the Al-Qur’an. The aim of this research is to obtain and overview objective regarding (1) the interpretation of surah al-Najm verse 49 in Thantawi jauhari’s tafsir al-Jawahir, (2) the nature of the shi’ra star in the Jawahir’s tafsir. This type of research is library research with a qualitative approach. And library research is library research that limits its study to library collection materials without field research. His results interpreted that, it was very natural for him to mention the Shi’ra> star and its submission to Allah after it was explained in the QS. al-Najm: 49 explanation above is that only He, the Almighty, is the Lord who is the Sustainer and Controller of the Shi’ra> stars. The purpose and content of the verse, as well as the explanation received by Thantawi, begins his interpretation by interpreting the meanings of the verse in the subsection that follow. Distinguishing the name Shi’ra> star from other celestial planets which are bigger and more sparkling, because this star was worshiped during the Jahiliyah era, those who worshiped it were the Khuza’ah people. The person who performed this worship was Abu Kabsyah. A explained as a double star, namely al-‘Ubur and Ghumaisho’, and what is visible from the earth is al-‘Ubur.